2016
DOI: 10.1074/jbc.m116.745414
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Disruption of the Oct4/Sox2 Protein Interaction Reveals Coordinated Mesendodermal Differentiation and the Epithelial-Mesenchymal Transition

Abstract: Although the Oct4/Sox2 complex is crucial for maintaining the pluripotency of stem cells, the molecular basis underlying its regulation during lineage-specific differentiation remains unknown. Here, we revealed that the highly conserved Oct4/Lys-156 is important for maintaining the stability of the Oct4 protein and the intermolecular salt bridge between Oct4/Lys-151 and Sox2/Asp-107 that contributes to the Oct4/Sox2 interaction. Post-translational modifications at Lys-156 and K156N, a somatic mutation detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
(66 reference statements)
2
18
1
1
Order By: Relevance
“…The distributions and median expression levels of these proteins were similar to those of wild‐type E14 ES cells (Fig D). We also found the half‐lives of both OCT4‐HALO (7.8 ± 1.3 h) and SOX2‐SNAP (8.1 ± 1.0 h) to be close to published half‐life values for these proteins (Fang et al , ; Pan et al , ; Liu et al , ) (Fig E and Table EV1), and the average cell cycle length of SBROS and wild‐type E14 ES cells were similar (Fig F and Table EV2). mRNA levels of pluripotency markers of SBROS cells were mostly unaltered (Fig EV1E and Table EV3).…”
Section: Resultssupporting
confidence: 85%
“…The distributions and median expression levels of these proteins were similar to those of wild‐type E14 ES cells (Fig D). We also found the half‐lives of both OCT4‐HALO (7.8 ± 1.3 h) and SOX2‐SNAP (8.1 ± 1.0 h) to be close to published half‐life values for these proteins (Fang et al , ; Pan et al , ; Liu et al , ) (Fig E and Table EV1), and the average cell cycle length of SBROS and wild‐type E14 ES cells were similar (Fig F and Table EV2). mRNA levels of pluripotency markers of SBROS cells were mostly unaltered (Fig EV1E and Table EV3).…”
Section: Resultssupporting
confidence: 85%
“…The distributions and median expression levels of these proteins were similar to those of wild type E14 ES cells ( Fig.1d). We also found the half-lives of both OCT4-HALO (7.8 ±1.3 h) and SOX2-SNAP (8.1 ±1.0 h) to be close to published half-life values for these proteins (Pan et al, 2016;Fang et al, 2014;Liu et al, 2017a) (Fig.1e), and the average cell cycle length of SBROS and wild type E14 ES cells were similar (Fig.1f). mRNA levels of pluripotency markers of SBROS cells were mostly unaltered ( Supplementary Fig.1e).…”
Section: Generation Of a Sox2-snap / Oct4-halo Knock-in Es Cell Linesupporting
confidence: 74%
“…2D). Since OCT4 and SOX2 can form a complex, bind to downstream target genes, and maintain the pluripotency32, the multiple transduction of OSKM factors were applied. Results showed that OCT4-SOX2 complex as well as OSK and OSM combinants could significantly reduce EpCAM promoter activity, but combinations of OCT4-KLF4, OCT4-c-MYC, SOX2-KLF4, SOX2-c-MYC, and KLF4-c-MYC did not influence EpCAM activity.…”
Section: Resultsmentioning
confidence: 99%